Pengembangan Bahan Ajar Cetak IPA Terintegrasi Augmented Reality 2D Materi Sistem Tata Surya untuk Siswa Sekolah Dasar - Istilanjar Sari; Wardani, Erika Fitri; Kurnia, Feni (Universitas Muhammadiyah Bangka Belitung, 2023)
Teachers' limited ability to produce their own media, particularly in relation to solar system content, prompted this investigation. InFocus has been their sole source for visual content. Accordingly, it is important to create printed scientific teaching materials that use 2D augmented reality as a kind of educational innovation. The goal of this research was to develop solar system-focused primary school learning products that combine 2D augmented reality with authentic and practical printed scientific teaching resources.The research and development (R&D) process employed in this study followed the ADDIE model's five steps: analysis, design, development, implementation, and evaluation. Thirty-seven sixth-graders from SD Negeri 42 Pangkalpinang participated in the research. Quantitative descriptions, in the form of data collected by 2 media experts and 2 material experts, were used to describe the data's validity. The results of a survey or survey provide information on practicality. Media validator scored 92% (Very Valid) and material validator scored 86% (Very Valid) in the evaluation. Eighty-nine percent (Very Practical) was the outcome of the small-scale experiments, and 90% was the result of the large-scale trials. As a result, it is safe to say that solar system-themed augmented reality 2D content incorporated into printed scientific textbooks for primary school children is a viable and useful tool for education.